In vitro fermentation of diets including agroindustrial by-products in batch cultures of ruminal microorganisms from goats - Romero-Huelva M.; Carro M.D.; Molina Alcaide E. (Innovation for sustainability in sheep and goats, 2019)
In the last years, there has been an increasing interest in the use of alternative feeds, such as agroindustrial by-products, in ruminants feeding. The aim of the present work was to study the effects of including variable amounts of different by-products (tomato fruits, citrus pulp, brewer´s grains and brewer´s yeast), previously processed and dried, in the concentrate of dairy goats on in vitro ruminal fermentation. Six concentrates were formulated and mixed with alfalfa hay in 1:1 proportion before being fermented in vitro using batch cultures of mixed rumen microorganisms from goats. The kinetics of gas production was evaluated in 72-h incubations and the fermentation variables were determined after 24 h incubation. Gas production data were adjusted to the exponential model y = A [1 – e (-c•t)]. There were no differences among diets either on pH (P = 0.091) or molar proportions (P = 0.613 to 0.999) of individual volatile fatty acids (VFA), but total VFA production was greater (P < 0.005) and the amount of CH4 was lower (P < 0.001) in five of the diets including by-products compared with the control diet. The inclusion of by-products resulted in greater values of gas production and gas production rate (P < 0.004 and 0.001, respectively) in four of the diets. The results of this study indicate that by-products from tomato and citrus juice and beer industry could be included in ruminant’s diets, promoting better ruminal fermentation pattern and reducing the environmental impact of animal production. The potential of agro-industrial by-products to substitute conventional ingredients in small ruminant diets should be further investigated.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)